Measurement and mapping of the GSM-based electromagnetic pollution in the Black Sea region of Turkey. (3rd April 2017) - Tuysuz, Burak; Mahmutoglu, Yigit
ABSTRACT: Electromagnetic pollution caused by mobile communication devices, a new form of environmental pollution, has been one of the most concerning problems to date. Consequences of long-term exposure to the electromagnetic radiation caused by cell phone towers are still unknown and can potentially be a new health hazard. It is important to measure, analyze and map the electromagnetic radiation levels periodically because of the potential risks. The electromagnetic pollution maps can be used for the detection of diseases caused by the radiation. With the help of the radiation maps of different regions, comparative analysis can be provided and distribution of the diseases can be investigated. In this article, Global System for Mobile communication (GSM)-based electromagnetic pollution map of the Rize Providence, which has high cancer rates because of the Chernobyl nuclear explosion, is generated. First, locations of the GSM base stations are identified and according to the antenna types of the base stations, safety distances are determined. Subsequently, 155 measurements are taken during November 2014 from the nearest living quarters of the Rize city center in Turkey. The measurements are then assessed statistically. Thenceforth, for visual judgment of the determined statistics, collected measurements are presented on the map. It is observed that national limits are not exceeded, but it is also discovered that the safety distance is waived at some of the measurement points and above the average radiation levels are noted. Even if the national limits are not exceeded, the long-term effects of the exposition to the electromagnetic radiation can cause serious health problems.